2011
DOI: 10.1002/mds.23476
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease sleep scale—validation of the revised version PDSS‐2

Abstract: The PDSS-2, with an extended spectrum of nocturnal disabilities and easier use for patients, is a reliable, valid, precise, and potentially treatment-responsive tool for measuring sleep disorders in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
273
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 311 publications
(314 citation statements)
references
References 38 publications
(62 reference statements)
22
273
3
3
Order By: Relevance
“…Similarly to the original validation study 5 , we also observed high correlation between PDSS-2 and PDQ-39 Summary Index, an indicator of the contribution of sleep problems to impaired health-related quality of life. Similarly to the original PDSS-2 validation study, we also revealed low correlation between the PDSS-2 (nocturnal problems) with ESS (daytime sleepiness) and neurocognitive tests.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similarly to the original validation study 5 , we also observed high correlation between PDSS-2 and PDQ-39 Summary Index, an indicator of the contribution of sleep problems to impaired health-related quality of life. Similarly to the original PDSS-2 validation study, we also revealed low correlation between the PDSS-2 (nocturnal problems) with ESS (daytime sleepiness) and neurocognitive tests.…”
Section: Discussionsupporting
confidence: 81%
“…To overcome these disadvantages, a new scale, the Parkinson's Disease Sleep Scale 2 nd version (PDSS-2), was developed and published in 2011 5 . It is composed of 15 items evaluating three domains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequently used scales for assessment of sleep disorders include the Parkinson Disease Sleep Scale (PDSS) 4 , Parkinson Disease Sleep Scale -2 (PDSS-2) 5 , Scales for Outcomes in PD-Sleep (SCOPA-Sleep scale) 6 , Epworth Sleepiness Scale (ESS) 7 and the Pittsburgh sleep quality index (PSQI) 8 . Clinical evaluation may be not enough to accurately diagnose sleep disorders.…”
mentioning
confidence: 99%